S100A4 contributes to colorectal carcinoma aggressive behavior and to chemoradiotherapy resistance in locally advanced rectal carcinoma - Yohei Harada; Sayako Ikeda; Yuna Kawabe; Yasuko Oguri; Miki Hashimura; Ako Yokoi; Akiko Sida; Naomi Fukagawa; Misato Hayashi; Mototsugu Ono; Chika Kusano; Hiroyuki Takahashi; et al. (Scientific Reports)
Abstract To investigate the functional role of S100A4 in advanced colorectal carcinoma (Ad-CRC) and locally advanced rectal carcinoma (LAd-RC) receiving neoadjuvant chemoradiotherapy (NCRT). We analyzed histopathological and immunohistochemical sections from 150 patients with Ad-CRC and 177 LAd-RC patients treated with NCRT. S100A4 knockout (KO) HCT116 cells were also used. S100A4 expression was absent in normal mucosa but increased progressively from colorectal adenoma to carcinoma, suggesting that S100A4 regulation is an early event in colorectal carcinogenesis. In Ad-CRC, high S100A4 expression correlated with high tumor budding and nuclear β-catenin, deep invasion, lymph-vascular involvement, and unfavorable prognosis. In NCRT-treated LAd-RC, high S100A4 expression was associated with poor treatment response and short progression-free survival. S100A4 KO decreased the proliferation of HCT116 cells through activation of the p53/p21waf1 axis, and sensitized cells to adriamycin-induced apoptosis. Levels of the apoptotic marker, cleaved poly (ADP-ribose) polymerase 1, were significantly higher in samples with low S100A4 and wild type p53. Finally, we observed a direct interaction between S100A4 and p53. In conclusion, S100A4 expression engenders aggressive behavior in Ad-CRC through association with β-catenin-driven tumor buddings. S100A4 exerts anti-apoptotic and proliferative effects via inhibition of p53 in LAd-RC patients receiving NCRT, which leads to chemoradioresistance and poor prognosis.